2008
DOI: 10.3382/ps.2008-00038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Litter Substrate and Genotype on Layers' Use of Litter, Exterior Appearance, and Heterophil:Lymphocyte Ratios in Furnished Cages

Abstract: Effects of sand versus sawdust as a litter bath substrate in furnished cages for laying hens were studied. The study used 112 Hy-Line White (HYW) and 140 Hy-Line Brown (HYB) layers housed in 18 furnished cages with 14 hens in each cage, generating 4 or 5 replicates per combination of genotype and litter substrate. Traits studied were mortality, feather cover, hygiene of hens, pecking wounds, heterophil/lymphocyte ratios, and hens' use of litter baths. Hens' litter bath use was measured by direct observations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Differently from , Wall et al (2008) observed that Hy-Line White and Hy-Line Brown layers housed in furnished cages preferred sawdust, and not sand, to dust bathe. However, no differences were detected in the time they remained on each substrate.…”
Section: Dust Bathingmentioning
confidence: 77%
“…Differently from , Wall et al (2008) observed that Hy-Line White and Hy-Line Brown layers housed in furnished cages preferred sawdust, and not sand, to dust bathe. However, no differences were detected in the time they remained on each substrate.…”
Section: Dust Bathingmentioning
confidence: 77%
“…Colored polypropylene string bunches were hung in the cages for pecking (Jones et al 2002). The top of the nest box was turned into a sand box using 6 cm height laths mounted on the margins of the roof (Wall et al 2008a). The nest boxes were built of water-resistant plywood with dimensions of 30 cm × 45 cm × 17 cm (width × length × height).…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…Blood (n=10 per treatment) was collected from the wing vein at 22 weeks of age, smears were prepared, and lymphocytes were counted at ×40 (oil immersion lens). Heterophil:lymphocyte (H/L) ratio was calculated according to Wall et al (2008).…”
Section: Ovarian Morphology and Reproductive Hormone Measurementsmentioning
confidence: 99%